PROPHETIC LEADERSHIP: REVITALISASI KEPEMIMPINAN PROFETIK DIERA SOCIETY 5.0 DALAM BINGKAI NASIONALISME - Aminuddin, M. Yusuf (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
Leadership is an element that cannot be avoide in life. it is human nature to always form a community with leaders who can advance the organization. In the context of good leadership is someone who has spiritual,social capabilities and can control himself and can influence, invite, move, and guide others to achieve common goals as taught by the prophets. The purpose of thus study was to determine the revitalization of prophetic leadership in the era of society 5.0 within the framework of nationalism. The reseacrch method used is descriptive qualitative with library research techniques. The results of the study show that the discussion of prophetic leadership in the era of socienty .0 within the framework of nasionalism shows yhat leadership currently requires a balance in framing a good civilization,by being a super smart leader in various fields by not forgetting the guidance of spiritual leadership values that are invited by prophet